Manajemen Rantai Nilai Jeruk Madu di Desa Barus Jahe Kecamatan Barus Jahe Kabupaten Karo Sumatra Utara - TARIGAN, RINA JULIANA; DARMAWAN, DWI PUTRA; ADI PUTRA, I GEDE SETIAWAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.2, No.4, Oktober 2013, 2013)
ABSTRACT Orange Honey Value Chain Management at Barus Jahe Sub-District Barus Jahe Regency Karo, North Sumatra. Orange is kind of horticulture are much favored by the public. One of the problems for citrus growers are constrained in citrus marketing system that is less efficient. therefore needs required a citrus marketing system that is efficient and provides benefits for farmers to sell their products without spending a huge cost. This study aimed to determine (1) the pattern of commodity value chains honey orange at Barus Jahe. (2) may at any gains in the value chain. (3) the effect on value chain management at Barus Jahe. The research was conducted in Barus Ginger, North Sumatra. Data obtained from this village were analyzed using descriptive methods. The study found that the value chain system in the village is divided into three, namely (1) farmers - traders - market - consumers. (2) farmers - market - retailer - consumer. (3) farmers - merchants - retailers - agents - consumers. Value chain lies in achieving the highest sales channel III. Marketing margins in the channel I Rp. 2500 (25%), channel II Rp. 3000 (30%), channell III Rp. 4500 (45%). The results of the analysis of value chain management applications that occurred in the study area is said to run pretty good. Key words : value chain, orange honey, value chain management